从新加坡的全球化中看潮州八邑会馆的转型 = Looking at the transformation of the Teochew Poit Ip Huay Kuan from the globalisation of Singapore - 陈思敏 Tan, Si Min (2019)
独立后，新加坡政府取代了宗乡会馆的传统功能，致使它们必须制定新策略，以适应时势的发展。1980年代以后，全球化给这些会馆带来转型的契机。从苏联解体、通讯科技变革到全球市场整合，全球化促进了“世界不断增强的联系”，给新加坡社会带来许多变化。在全球化治理上，新加坡政府提出了“迈向全球，扎根本土”的策略，并号召宗乡会馆在促进经济联系、文化传承与社会和谐方面给予帮助。以新加坡潮州八邑会馆作为研究案例，本文将分析会馆在新加坡的经济、文化与社会全球化下，如何根据实际情况，作出相应的调整以在变迁的社会中生存与发展。Since gaining independence, the Singapore government has replaced most of the traditional functions of the Chinese clan associations, who must develop new strategies to adapt to the changing needs of the society. After the 1980s, globalisation has provided these Chinese clan associations with opportunities to transform. From the disintegration of the Soviet Union, ICT revolution and global market integration, globalisation has caused the world to become increasingly connected, and brought various changes to Singapore’s society. To manage globalisation, Singapore government proposed the strategy of "Go global, stay local", and called upon the Chinese clan associations to assist in building economic ties, promoting traditional culture and developing a harmonious society. Taking Singapore Teochew Poit Ip Huay Kuan as a case study, this thesis aims to see how the traditional clan associations, under the economic, cultural and social globalisation of Singapore, transformed itself to survive and develop in the changing society.